2008
DOI: 10.1136/aim.26.2.69
|View full text |Cite
|
Sign up to set email alerts
|

A Blinded Randomised Trial of Acupuncture (Manual and Electroacupuncture) Compared with a Non-Penetrating Sham for the Symptoms of Osteoarthritis of the Knee

Abstract: Objectives To compare the effect of acupuncture (manual and electroacupuncture) with that of a nonpenetrating sham ('placebo' needle) in patients with osteoarthritic knee pain and disability who are blind to the treatment allocation. Methods Acupuncture naïve patients with symptomatic and radiological evidence of osteoarthritis of the knee were randomly allocated to a course of either acupuncture or non-penetrating sham acupuncture using a sheathed 'placebo' needle system. Acupuncture points for pain and stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 41 publications
0
83
0
Order By: Relevance
“…2 Randomized controlled trials examining the effects of acupuncture have started to use these sham devices and needles. [3][4][5] Studies examining the blinding effectiveness of the sham devices usually investigate similarities between the sensory intensities elicited by the sham and real needles that are felt by the participants. 1 If the sensory intensities to both needle types are not statistically different from each other, then it is indirectly inferred that the sham device is capable of blinding the participant.…”
mentioning
confidence: 99%
“…2 Randomized controlled trials examining the effects of acupuncture have started to use these sham devices and needles. [3][4][5] Studies examining the blinding effectiveness of the sham devices usually investigate similarities between the sensory intensities elicited by the sham and real needles that are felt by the participants. 1 If the sensory intensities to both needle types are not statistically different from each other, then it is indirectly inferred that the sham device is capable of blinding the participant.…”
mentioning
confidence: 99%
“…1 2 Randomised controlled trials examining the effects of acupuncture have started to use these sham devices and needles. [3][4][5] Credibility studies had generally found that the participantblinding effectiveness of these sham devices were fair or good. [6][7][8] Studies examining the blinding effectiveness of the sham devices usually use only one or a small number of acupoints.…”
Section: Introductionmentioning
confidence: 99%
“…However, development of methods able to induce the committed differentiation of stem cells, has become the focus of tissue engineering development. Thus, an effective and safe modality of induction is valuable since potential safety concerns have arisen from the previous differentiation of BMSCs induced by agents (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture (EA) is a modified acupuncture technique that utilizes electrical stimulation. Previous studies have demonstrated that EA has therapeutic effects on chondral defects including knee osteoarthritis (10)(11)(12) and produces cytokines with multiple biological activities in various types of diseases (13)(14)(15). In addition, animal experiments have shown that EA enhances BMSC differentiation into neuronal cells (16).…”
Section: Introductionmentioning
confidence: 99%